Positive electrode material and preparation method thereof, and secondary battery and electric device comprising positive electrode material

CN119731806AActive Publication Date: 2025-03-28CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202280007819.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-12-01
Publication Date
2025-03-28
Estimated Expiration
2042-12-01

AI Technical Summary

Technical Problem

Existing lithium-ion battery cathode materials are prone to particle cracking and pulverization during the cycle process, poor cycle performance, high impurity lithium, and gas expansion, resulting in poor storage and safety performance.

Method used

The cathode material with the chemical composition of Li1+a[NixCoyMnzMbWc]O2 is used, in which M is selected from Mo, Zr, Al, Ti and other elements, W is enriched at the grain boundaries of the substrate particles, and the combined coating layer contains W, Co, Al and B elements improve the structural stability and cycle performance of the material through specific preparation methods.

Benefits of technology

It achieves high discharge specific capacity, good cycle performance, low impurity lithium content and less gas production, improving the overall performance and safety performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119731806A_ABST
    Figure CN119731806A_ABST
Patent Text Reader

Abstract

The present application provides a positive electrode material comprising base material particles of formula (I): Li1 + a [NixCoyMnzMbWc] O2 (I) wherein M is selected from one or more of Mo, Zr, Al, Ti, Sb, Nb, Te, Mg, Al, Ca, Zn and Sr, 0.6 lt; xlt; 1, 0lt; yt; Yt; 0 1t, 0.4, 0 1t; zlt, zlt; 0 1t, 0.4, 0 1t; a < lt >; 0, 0, 0, 0; blt; 0.1, 0 lt; clt; ct; 0.1, x + y + z + b + c = 1; and W is enriched at the grain boundary of the substrate particles. The positive electrode material disclosed by the invention has relatively high specific capacity, relatively good cycle performance, relatively high compaction density and reduced lithium impurity amount and gas production. The invention also provides a method for preparing the positive electrode material, and a positive electrode plate, a secondary battery and an electric device comprising the positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Positive Electrode Material, Preparation Method Thereof, Secondary Battery Containing the Same, and Electric Appliance Technical Field

[0001] The present application relates to the technical field of lithium batteries, and particularly to a positive electrode material, a preparation method thereof, a secondary battery containing the positive electrode material, and an electric appliance. Background Art

[0002] Lithium ion batteries have been increasingly favored by the battery industry due to their advantages of light weight, long life, and environmental friendliness. The positive electrode material of lithium ion batteries has always been the focus of research and development in the industry. Currently, the mainstream positive electrode materials of lithium ion batteries, with their characteristics of high capacity and high energy density, meet the requirements of increasingly high energy density and are more favored. However, such positive electrode materials have poor capacity, and may have problems such as particle cracking, pulverization during cycling, poor cycling performance, high impurity lithium content, easy gas generation, and poor safety performance.

[0003] Therefore, there is a need in the art for a positive electrode material that can improve at least one of the above problems and has good performance.

[0004] Summary of the Invention

[0005] The present application is made in view of the above problems, and its purpose is to provide a positive electrode material including substrate particles with a chemical composition of formula (I):

[0006] Li 1+a [Ni[[ID=,25]] x Co y Mn z M b W c O2 (I)

[0007] Wherein, M is selected from one or more of Mo, Zr, Al, Ti, Sb, Nb, Te, Mg, Al, Ca, Zn, and Sr, 0.6 ≤ x < 1, 0 < y < 0.4, 0 < z < 0.4, 0 < a < 0.2, 0 < b < 0.1, 0 < c < 0.1, and x + y + z + b + c = 1; and W is enriched at the grain boundaries of the substrate particles. The positive electrode material of the present application has good comprehensive performance: high discharge specific capacity, good cycling performance, low impurity lithium content, and less gas generation.

[0008] In any embodiment, formula (I) satisfies one or more of the following conditions (1) to (8):

[0009] (1) M is selected from one or more of Zr, Al, Mg, and Ti;

[0010] (2) 0.8 ≤ x < 1;

[0011] (3)0 <a<0.08;

[0012] (4)0 <b<0.018;

[0013] (5)0 <c<0.0013;

[0014] (6) b:c = 0.076 to 384, optionally b:c = 5 to 69, more optionally b:c = 13 to 69;

[0015] (7) (1+a): (x+y+z) = 1.01 to 1.25, optionally (1+a): (x+y+z) = 1.05 to 1.15;

[0016] (8) The doping weight of the M element is greater than or equal to the doping weight of the W element. Optionally, the weight ratio of the M element to the tungsten (W) element is 1:(0.1-1), more preferably 1:(0.1-0.5). A positive electrode material that meets one or more of the above conditions has better performance.

[0017] In any embodiment, in the substrate particles, the W content within a thickness of 40 nm from the grain boundary is at least 80% by weight, and optionally at least 90% by weight, based on the total weight of W in the substrate particles. Almost all of the W element doped in the material is concentrated at the grain boundaries, which helps increase compaction density and improve various properties.

[0018] In any embodiment, based on the total weight of the substrate particles, the W content in the substrate particles is 100 to 200,000 ppm, optionally 100 to 3,000 ppm, and more optionally 500 to 2,500 ppm, which is beneficial for improving particle integrity and cycle performance.

[0019] In any embodiment, the volume particle size distribution diameter (D v 90-D v 10) / D v 50 is 1.1 to 1.8, optionally 1.2 to 1.5, more preferably 1.25 to 1.45. This is conducive to achieving higher compaction density, increasing capacity, etc.

[0020] In any embodiment, the positive electrode material further includes a coating layer disposed on the surface of the substrate particles, wherein the coating layer comprises at least one of W, Co, Al, and B. Alternatively, the coating layer comprises at least W and / or B. More preferably, the coating layer comprises W, Co, Al, and B. This further improves the material's cycling performance, reduces the impurity lithium content, and improves safety.

[0021] In any embodiment, the coating layer satisfies one or more of the following conditions (1) to (5):

[0022] (1) The coating layer contains 100 ppm to 2000 ppm, optionally 500 ppm to 1000 ppm of W element, based on the total weight of the substrate particles;

[0023] (2) The coating layer contains 100 ppm to 16000 ppm, optionally 1000 ppm to 13000 ppm of Co element, based on the total weight of the substrate particles;

[0024] (3) The coating layer contains 100 ppm to 3000 ppm, optionally 500 ppm to 2000 ppm of Al element, based on the total weight of the substrate particles;

[0025] (4) The coating layer contains 100 ppm to 2000 ppm, optionally 500 ppm to 1500 ppm of B element, based on the total weight of the substrate particles;

[0026] (5) The coating layer contains W, Co, Al and B elements and the total amount of these four elements is 1000 to 22000 ppm, preferably 1000 to 15000 ppm, based on the total weight of the substrate particles. Coating various elements within such a range is more conducive to improving the performance of the material.

[0027] The second aspect of the present application provides a method for preparing a cathode material, and the cathode material includes substrate particles with a chemical composition of formula (I):

[0028] Li 1+a [Ni x Co y Mn z M b W c O2 (I)

[0029] where M is selected from one or more of Mo, Zr, Al, Ti, Sb, Nb, Te, Mg, Al, Ca, Zn and Sr, 0.6 ≤ x < 1, 0 < y < 0.4, 0 < z < 0.4, 0 < a < 0.2, 0 < b < 0.1, 0 < c < 0.1, and x + y + z + b + c = 1; and W is enriched at the grain boundaries of the substrate particles;

[0030] The method includes the following steps:

[0031] - S0: Provide a precursor material with a chemical composition of Ni x Co y Mn z (OH)2, 0.6 ≤ x < 1, 0 < y < 0.4, 0 < z < 0.4, and x + y + z = 1,

[0032] -S1: Grinding and mixing the precursor material and the W source compound, then adding the Li source compound and the M source compound to the mixture and thoroughly mixing, and sintering the mixture to obtain the substrate particles. The positive electrode material prepared using the method of this application has excellent comprehensive performance: high capacity, good cycle performance, low impurity lithium content, and safety performance.

[0033] In any embodiment, the W source compound particles have a particle size of 20 to 500 nm, optionally 50 to 300 nm; and / or the W source compound is selected from one or more of WO3, H2WO4, Li2WO4, (NH4)2WO4, MgWO4, and Zr(WO3)2; optionally, one or more of WO3, H2WO4, and Li2WO4; and / or the W element is added in an amount of 100 to 200,000 ppm, optionally 100 to 3,000 ppm, and more optionally 500 to 2,500 ppm, based on the total weight of the precursor material. The use of the above W source compound and its particle size facilitates the doping of the W element into the grain boundaries of the material during high-temperature sintering.

[0034] In any embodiment, the M source compound is selected from sulfates, nitrates, chlorides, carbonates, oxides, hydroxides, oxalates, and acetates containing the M element, and is optionally an oxide of the M element. Optionally, the M element is one or more of Zr, Al, Mg, and Ti. Optionally, the M element is added in an amount of 100 to 5000 ppm, preferably 500 to 3000 ppm, based on the total weight of the precursor material. These M-containing compounds are more conducive to uniformly doping the M element into the layered material lattice at high temperatures, and using such an addition amount is more conducive to improving the material's performance.

[0035] In any embodiment, step S1 satisfies at least one of the following conditions:

[0036] (1) The added weight ratio of the M element to the W element is 1:(0.1-1), optionally 1:(0.1-0.5);

[0037] (2) The ratio of the molar amount of Li atoms to the total molar amount of Ni, Co, and Mn atoms is set to 1.01 to 1.25, and optionally 1.05 to 1.15.

[0038] This enables the obtained positive electrode material to have a higher discharge specific capacity and better cycle performance.

[0039] In any embodiment, the grinding and mixing is performed using mechanical milling or ball milling. Optionally, the grinding and mixing is performed in a ball mill, or optionally in a heated ball mill. Optionally, the grinding speed is 500 to 3000 r / min, or alternatively 1000 to 2000 r / min, or 800 to 1500 r / min. Optionally, the grinding and mixing is performed at a temperature of 30 to 100° C., or alternatively 40 to 60° C. These process conditions promote uniform mixing and stable adhesion of the W source compound and the precursor material, facilitating W doping enrichment at grain boundaries.

[0040] In any embodiment, the method further comprises the step of providing a coating layer on the surface of the substrate particles, which comprises:

[0041] - S2: mixing the substrate particles obtained in S1 with a W-containing compound and / or a Co-containing compound and sintering; and / or

[0042] - S3: The substrate particles obtained from S1 or the sintered product obtained from S2 are mixed with an Al-containing compound and / or a B-containing compound and then sintered.

[0043] By coating the substrate particles using the above coating steps, the material properties are further improved.

[0044] In any embodiment, step S2 satisfies one or more of the following conditions:

[0045] (1) The W-containing compound is selected from one or more of WO3, H2WO4, Li2WO4, (NH4)2WO4, MgWO4, and Zr(WO3)2;

[0046] (2) The amount of W element added is 100-2000 ppm, optionally 500-1000 ppm, based on the total weight of the precursor material. This is beneficial for making the W-containing coating layer more uniform and improving the material properties.

[0047] In any embodiment, step S2 satisfies one or more of the following conditions:

[0048] (1) The Co-containing compound is selected from one or more of Co3O4, Co(OH)2, CoO, CoOOH, Co(CH3COO)2, CoC2O4, and CoCO3;

[0049] (2) The amount of Co added is 100 to 16,000 ppm, preferably 1,000 to 13,000 ppm, based on the total weight of the precursor material. This is more conducive to reducing surface impurities and improving cycle performance.

[0050] In any embodiment, in step S3, the Al-containing compound is selected from one or more of Al2O3, Al(OH)3, Al2(SO4)3, AlCl3, and Al(NO3)3; and / or the amount of Al added is 100-3000 ppm, preferably 500-2000 ppm, based on the total weight of the precursor material. This can further enhance the interfacial stability of the material particles and reduce interfacial side reactions, thereby further improving the recycling, storage, and safety performance of the material.

[0051] In any embodiment, in step S3, the B-containing compound is selected from one or more of BCl3, B2(SO4)3, B(NO3)3, BN, B2O3, BF3, BBr3, BI3, H2BO5P, H3BO3, C5H6B(OH)2, C3H9B3O6, (C2H5O)3B, and (C3H7O)3B, and / or the amount of B added is 100 to 2000 ppm, preferably 500 to 1500 ppm, based on the total weight of the precursor material. This can further reduce the content of impurities on the surface of the material while increasing the capacity of the material. In addition, it can further improve the interfacial side reactions of the material and enhance the circulation, storage, and safety performance of the material.

[0052] In any embodiment, the volume particle size distribution diameter of the precursor material is 1.1 to 1.8, optionally 1.2 to 1.5; and / or the D of the precursor material is v 50 is 5 μm to 15 μm, optionally 5 μm to 10 μm, which is beneficial for obtaining a desired positive electrode material with a larger compaction density, thereby facilitating the realization of a higher capacity.

[0053] A third aspect of the present application provides a secondary battery, comprising the positive electrode material of the first aspect or the positive electrode material obtained by the method of the second aspect.

[0054] A fourth aspect of the present application provides an electrical device comprising a secondary battery selected from the group consisting of:

[0055] The positive electrode material of the present application has good comprehensive performance: higher capacity, better cycle performance, lower amount of impurity lithium and lower gas production. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] FIG1 is a schematic diagram of a secondary battery according to an embodiment of the present application.

[0057] FIG. 2 is an exploded view of the secondary battery according to the embodiment of the present application shown in FIG. 1 .

[0058] FIG3 is a schematic diagram of a battery module according to an embodiment of the present application.

[0059] FIG4 is a schematic diagram of a battery pack according to an embodiment of the present application.

[0060] FIG. 5 is an exploded view of the battery pack shown in FIG. 4 according to an embodiment of the present application.

[0061] FIG6 is a schematic diagram of an electric device using a secondary battery as a power source according to an embodiment of the present application.

[0062] Description of reference numerals:

[0063] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 housing; 52 electrode assembly; 53 top cover assembly DETAILED DESCRIPTION

[0064] Below, the positive electrode material and its preparation method of the present application, as well as the embodiments of the positive electrode sheet, secondary battery and electrical device containing the positive electrode material are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0065] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0066] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0067] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0068] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0069] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.

[0070] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0071] Lithium-ion batteries (lithium secondary batteries) are increasingly favored by the battery industry for their advantages of lightweight, long life, cleanliness and environmental protection. As the key material, the positive electrode material of lithium-ion batteries has always been the focus of research and development in the industry. At present, the mainstream positive electrode materials of lithium-ion batteries are lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide and nickel-cobalt-manganese ternary materials, and emerging materials such as NCA (nickel-cobalt-aluminum) system and LOL (lithium-rich manganese solid solution) have been added to them and have been widely used commercially. Among them, ternary materials, especially NCA materials, meet the requirements of increasingly higher energy density with their high capacity and high energy density, and are more popular.

[0072] However, the ternary positive electrode materials in the existing technology are prone to cracking and pulverization of material particles during the lithium insertion and extraction process, resulting in poor cycle performance. In addition, the existing materials also have high levels of impure lithium and gas expansion, resulting in poor storage and safety performance.

[0073] In view of the above deficiencies of such materials in the prior art, the present application provides a cathode material and a preparation method thereof. The cathode material of the present application has a high capacity, improved material structure stability and particle integrity, thereby enhancing the long-cycle performance. At the same time, it also has a reduced content of lithium impurities and gas generation, thereby improving the storage and safety performance.

[0074] Cathode material

[0075] In one embodiment of the present application, a cathode material is proposed, which includes substrate particles with a chemical composition of formula (I):

[0076] Li 1+a [Ni x Co y Mn z M b W c O2 (I)

[0077] Wherein, M is selected from one or more of Mo, Zr, Al, Ti, Sb, Nb, Te, Mg, Al, Ca, Zn, and Sr, 0.6 ≤ x < 1, 0 < y < 0.4, 0 < z < 0.4, 0 < a < 0.2, 0 < b < 0.1, 0 < c < 0.1, and x + y + z + b + c = 1; and W is enriched at the grain boundaries of the substrate particles.

[0078] The cathode material of the present application has good comprehensive performance: high discharge specific capacity, good cycle performance, low lithium impurity content, and less gas generation.

[0079] In the cathode material of the present application, M element and tungsten (W) element are simultaneously doped and W is enriched at the grain boundaries in the substrate particles. This makes the material have good lattice structure stability and particle integrity, and thus has ideal comprehensive performance: good discharge specific capacity, improved cycle performance, reduced lithium impurity content, higher tap density, and improved safety performance.

[0080] For the doped M element, an element with a relative atomic mass < 150 or a stable valence state > +3 is selected as the M element. Such an M element has a small atomic mass and radius, has an appropriate electrostatic repulsion force with W, and has a relatively fast migration speed into the material during the sintering process, thereby inhibiting the migration of W into the material and making W more inclined to be enriched at the grain boundaries.

[0081] In this article, the "grain boundary" is the boundary between individual primary particles in a secondary particle.

[0082] In this text, fine particle units without agglomeration (e.g., single crystal particles) are referred to as "primary particles", and the particles formed after the agglomeration of primary particles are called "secondary particles". In this text, the substrate particles are secondary particles. When observed under a scanning electron microscope, the spherical ones are secondary particles, and the nanosheets that make up the secondary particles are primary particles.

[0083] In this text, the W element is enriched at the grain boundaries, that is, the W element is doped on the surfaces of each primary particle in the substrate particles.

[0084] In some embodiments, the M element is uniformly doped into the crystal structure of the substrate particles. In this text, "uniform doping" means being completely and evenly distributed inside the material particles (or in the crystal structure).

[0085] In some embodiments, in formula (I), M is selected from one or more of Zr, Al, Mg, and Ti. Doping these elements as the M element is more helpful for stabilizing the crystal structure of the material, promoting the enrichment of W at the grain boundaries, and thus improving the material properties.

[0086] In some embodiments, formula (I) satisfies 0.8 ≤ x < 1 and / or 0 < a < 0.08. In this application, the coefficients x and a can be conventional, but further controlling these values can help improve the material properties.

[0087] In some embodiments, formula (I) satisfies 0 < b < 0.018 and / or 0 < c < 0.0013. This helps to improve the cycling performance of the material, reduce the amount of parasitic lithium and the gas generation amount, and improve the safety performance.

[0088] In some embodiments, in formula (I), 0 < y < 0.1; and / or 0 < z < 0.1. In this application, the values of the coefficients y and z are conventional and not critical, and they can be within the above ranges.

[0089] In some embodiments, in formula (I), b:c = 0.076 - 384, optionally b:c = 5 - 69, and more optionally b:c = 13 - 69. Such a cathode material has better performance.

[0090] In some embodiments, formula (I) satisfies (1 + a):(x + y + z) = 1.01 - 1.25, optionally (1 + a):(x + y + z) = 1.05 - 1.15, then the performance of the cathode material is better.

[0091] In some embodiments, the doping weight of the M element is greater than or equal to the doping weight of the W element. Optionally, the weight ratio of the M element to the W element is 1:(0.1-1), more preferably 1:(0.1-0.5). The M element and the W element content satisfy the above relationship, which is more conducive to the enrichment of the W element at the grain boundary, and improves the structural stability and particle integrity of the material, and increases the active ions (such as Li + )’s migration ability in the material, improves cycle stability, increases compaction density, reduces the amount of impurity lithium, and improves safety performance.

[0092] In some embodiments, the W content within a thickness of 40 nm from the grain boundary in the substrate particles is at least 80%, and optionally at least 90%. In the cathode material of the present application, the doped W element is almost entirely concentrated at the grain boundaries, which is beneficial for improving the structural integrity and stability of the material particles, increasing the compaction density, and improving performance.

[0093] In some embodiments, the amount of W is 100-200,000 ppm, optionally 100-3,000 ppm, and more optionally 500-2,500 ppm, based on the total weight of the substrate particles. This helps improve particle integrity and cycle performance, while ensuring good electrochemical performance of the material.

[0094] Herein, the doping amount of the W element refers to the amount of the W element in the base material particles.

[0095] In some embodiments, based on the total weight of the substrate particles, the amount of M is 100-5000 ppm, alternatively 500-3000 ppm. Inclusion of M in such a range is more conducive to W enrichment at grain boundaries and helps the material obtain ideal properties.

[0096] In some embodiments, the volume particle size distribution diameter (D v 90-D v 10) / D v 50) is 1.1 to 1.8, optionally 1.2 to 1.5, and more optionally 1.25 to 1.45. The positive electrode material of the present application has a volume particle size distribution diameter within the above range, which is more conducive to achieving a higher compaction density (for example, a compaction density at 5 tons of pressure ≥3.45g / cc, or even ≥3.50g / cc), thereby facilitating the improvement of energy density and specific capacity.

[0097] In this paper, “volume particle size distribution diameter” is defined as (D v 90-D v 10) / D v The value of 50, where D v 90.D v 10 and Dv 50 represents the average particle size corresponding to 90%, 10% and 50% of the particles in the volume distribution. The volume particle size distribution distance reflects the particle size distribution width of the material particles - the larger the distance, the wider the particle size distribution width. v 90.D v 10 and D v 50 can be measured using conventional methods and instruments in the art (for example, using a laser particle size analyzer).

[0098] This article uses the parameter "compaction density" to quantitatively evaluate the hardness of the positive electrode material particles and the compaction density of the positive electrode sheet. The compaction density test can be carried out by any appropriate method known to those skilled in the art. In this article, a positive electrode material of a certain mass m is placed in a cylindrical mold with an inner radius of R, and different pressures are applied by a press to test the particle size distribution under different pressures until a double peak appears in the particle size distribution at a certain pressure (this indicates that there are a large number of compressed particles in the tested material). The density under this pressure is the compaction density; the higher the compaction density value, the higher the volume energy density of the material particles. The compaction density is calculated by the following formula:

[0099] Compacted density = m / (π·R 2 ·ΔH)

[0100] Where m is the mass of the material being tested added to the mold, R is the inner radius of the mold, and ΔH is the height difference before and after pressure is applied.

[0101] In some embodiments, the cathode material of the present application further includes a coating layer disposed on the surface of the substrate particles, wherein the coating layer comprises at least one of W, Co, Al, and B. The cathode material including the coating layer comprising at least one of the aforementioned elements can effectively reduce the surface impurity lithium content and / or inhibit interfacial side reactions, further improving at least one of the capacity, cycle performance, and safety performance of the cathode material.

[0102] As used herein, "miscellaneous lithium" has the meaning commonly understood by those skilled in the art, meaning lithium source compounds or their byproducts that are not completely reacted during the high-temperature sintering process of the material. Its accumulation on the surface of the material not only increases the active ion migration impedance, resulting in a decrease in capacity, but may also produce gases (such as CO2, etc.), increasing safety risks. Generally, miscellaneous lithium includes (but is not limited to) lithium carbonate and / or lithium hydroxide. The miscellaneous lithium content can be determined by any method known to those skilled in the art, for example, acid-base titration.

[0103] In some embodiments, the coating layer contains W and / or B elements; this is more conducive to improving the capacity and cycle performance of the material. In some embodiments, the coating layer includes W, Co, Al and B elements. This further improves the capacity and cycle performance of the material, and helps to reduce the content of impure lithium and safety performance. The W and / or Co coating layer can optimize the enrichment of W at the grain boundary, reduce impure lithium on the surface of the material, improve interface stability, and improve cycle performance; the B and / or Al coating layer is conducive to improving the specific capacity of the material, alleviating interface side reactions, and is conducive to the performance of the material's cycle performance.

[0104] In some embodiments, the coating layer contains 100ppm to 2000ppm, optionally 500ppm to 1000ppm of W element, based on the total weight of the substrate particles. In some embodiments, the coating layer contains 100ppm to 16000ppm, optionally 1000ppm to 13000ppm of Co element, based on the total weight of the substrate particles. In some embodiments, the coating layer contains 100ppm to 3000ppm, optionally 500ppm to 2000ppm of Al element, based on the total weight of the substrate particles. In some embodiments, the coating layer contains 100ppm to 2000ppm, optionally 500ppm to 1500ppm of B element, based on the total weight of the substrate particles. Coating various elements in such a range is more conducive to improving the performance of the material.

[0105] In some embodiments, the coating layer contains W, Co, Al, and B elements, and the total amount of these four elements is 1000 to 22000 ppm, preferably 1000 to 15000 ppm, based on the total weight of the substrate particles.

[0106] The presence and thickness of the coating layer can be confirmed using conventional methods and instruments, such as scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The coating layer can be observed as a separate layer outside the substrate particles under the microscope. The content of various elements in the coating layer can also be determined using conventional methods and instruments, such as quantitative elemental distribution analysis using EDS (Electron Spectroscopy) with a SEM.

[0107] In some embodiments, the coating layer has a thickness within a conventional range in the art; optionally, the coating layer has a thickness of 0.001 μm to 1 μm, and optionally, 0.01 μm to 0.5 μm. A coating layer thickness within the aforementioned range is more conducive to better electrochemical performance and volumetric energy density of the positive electrode material.

[0108] Preparation method

[0109] Another aspect of the present invention provides a method for preparing a cathode material of formula (I),

[0110] Li 1+a [Ni x Co y Mn z M b W c O₂ (I)

[0111] Wherein, M is selected from one or more of Mo, Zr, Al, Ti, Sb, Nb, Te, Mg, Al, Ca, Zn, and Sr, 0.6 ≤ x < 1, 0 < y < 0.4, 0 < z < 0.4, 0 < a < 0.2, 0 < b < 0.1, 0 < c < 0.1, and x + y + z + b + c = 1; and W is enriched at the grain boundaries of the substrate particles;

[0112] The method includes the following steps:

[0113] - S0: Provide a precursor material with a chemical composition of Ni x Co y Mn z (OH)₂, 0.6 ≤ x < 1, 0 < y < 0.4, 0 < z < 0.4, and x + y + z = 1;

[0114] - S1: Grind and mix the precursor material with a W source compound, then add a Li source compound and an M source compound thereto and mix well, and sinter the mixture to obtain the substrate particles. The cathode material prepared by the method of the present application has good comprehensive properties: high capacity, good cycle performance, low amount of lithium impurities, and safety performance.

[0115] In some embodiments, the particle size of the W source compound is 20 - 500 nm, optionally 50 - 300 nm. In the method of the present application, using a W source compound with the above particle size range makes it easier for W to be doped into the grain boundaries of the material during sintering.

[0116] In some embodiments, the W source compound is selected from one or more of WO₃, H₂WO₄, Li₂WO₄, (NH₄)₂WO₄, MgWO₄, and Zr(WO₃)₂; optionally, it is selected from one or more of WO₃, H₂WO₄, and Li₂WO₄. These W source compounds are more likely to promote the doping of W element into the grain boundaries of the material during high-temperature sintering.

[0117] In some embodiments, based on the total weight of the substrate particles, the addition amount of W element is 100 - 3000 ppm, optionally 500 - 2500 ppm. When the addition amount of W is within the above range, it is beneficial to improve the structural stability of the material, improve the cycle performance, and achieve a higher specific capacity.

[0118] In some embodiments, the M source compound is selected from sulfates, nitrates, chlorides, carbonates, oxides, hydroxides, oxalates, and acetates of the M element, and may alternatively be an oxide of the M element. In some embodiments, the M element is one or more of Zr, Al, Mg, and Ti. These compounds containing the M element are more conducive to uniformly doping the M element into the layered material lattice at high temperatures and achieving structural stability of the material.

[0119] In some embodiments, the amount of the M element added is 100 to 5000 ppm, or alternatively 500 to 3000 ppm, based on the total weight of the substrate particles, to improve the cycle stability and specific capacity of the positive electrode material.

[0120] In some embodiments, in step S1, the ratio of the added amount of the M element to the W element is 1:(0.1-1), optionally 1:(0.1-0.5). In this way, the obtained positive electrode material has better performance.

[0121] In some embodiments, in step S1, the ratio of the molar amount of Li atoms to the total molar amount of Ni, Co, and Mn atoms is set to 1.01 to 1.25, or alternatively, 1.05 to 1.15. Thus, the obtained positive electrode material has a higher discharge capacity and better cycle performance (for example, the material is less likely to undergo irreversible phase transition during cycling).

[0122] Herein, for simplicity, Me may be used to represent the total molar amount of Ni, Co, and Mn, and the ratio of the molar amount of Li atoms to the total molar amount of Ni, Co, and Mn atoms may be expressed as "Li / Me".

[0123] The lithium source compound can be any conventional lithium source compound known to those skilled in the art. In some embodiments, the lithium source compound is selected from one or more of LiOH·H2O, Li2CO3, Li2SO4, LiNO3, LiC2O4, CH3COOLi, and the like. Using such lithium source compounds can help the positive electrode material have a stable layered structure and ensure high electrochemical performance.

[0124] In some embodiments, the grinding and mixing is carried out by mechanical milling or ball milling. In some embodiments, the grinding and mixing is carried out in a ball mill, optionally in a heated ball mill. In some embodiments, optionally, the rotation speed of the ball mill is 500 to 3000 r / min, optionally 1000 to 2000 r / min. In some embodiments, the grinding and mixing is carried out at a temperature of 30 to 100° C., optionally 40 to 60° C. The above-mentioned process conditions can promote uniform mixing and stable adhesion of the W source compound and the precursor material, which is conducive to the enrichment of W doping at the grain boundaries.

[0125] In some embodiments, in step S1, the sintering is performed at a temperature of 650°C to 950°C. In some embodiments, the sintering is performed for 10 to 20 hours. In some embodiments, the sintering is performed in air or an O2 atmosphere. Using the above process conditions, the desired positive electrode material can be obtained.

[0126] In some embodiments, the method of the present application further comprises the step of providing a coating layer on the surface of the substrate particles, which comprises:

[0127] - S2: mixing the substrate particles obtained in S1 with a W-containing compound and / or a Co-containing compound and sintering; and / or

[0128] - S3: The substrate particles obtained from S1 or the sintered product obtained from S2 are mixed with an Al-containing compound and / or a B-containing compound and then sintered.

[0129] By coating the substrate particles with the above-mentioned coating step, the material properties are further improved. In the method of the present application, the coating of different elements is carried out in separate steps, not only based on the demand for sintering temperature to achieve the best coating effect of different elements, but also to enable different elements to be in a position in the coating layer that is more conducive to improving material properties. Compared with Al and / or B, the coating of W and / or Co is carried out first, that is, it is preferred that the coating containing W and / or Co is carried out directly on the surface of the substrate particles; in this way, the W element in the coating layer can supplement the insufficient W doping at the grain boundary in the S1 step, thereby helping to improve the integrity and cycle performance of the particles, and Co can reduce the impurity lithium content on the surface of the substrate particles, improve interface stability, and improve cycle performance. Coating the coated or uncoated substrate particles with Al and / or B elements is beneficial to reducing the interface side reactions between the material and the electrolyte, and increasing the capacity and improving the cycle performance of the material.

[0130] In some embodiments, in step S2, the W-containing compound has a conventional particle size, preferably 0.01 to 5 μm, more preferably 0.05 to 1 μm, and even more preferably 0.1 to 1 μm. Using W-containing compound materials with such a particle size range can make the coating more uniform.

[0131] In some embodiments, in step S2, the substrate particles obtained in step S1 are mixed with at least one W-containing compound and then sintered. In some embodiments, in step S2, the W-containing compound is selected from one or more of WO3, H2WO4, Li2WO4, (NH4)2WO4, MgWO4, and Zr(WO3)2. These W-containing compounds are more conducive to forming a stable coating layer, preventing direct contact between the electrolyte and the substrate particles, and suppressing interfacial side reactions.

[0132] In some embodiments, in step S2, based on the total weight of the precursor material, the amount of W added is 100-2000 ppm, optionally 100-1000 ppm. Adding W within the above range is more conducive to improving the recycling performance of the material.

[0133] In some embodiments, in step S2, the Co-containing compound is selected from one or more of Co3O4, Co(OH)2, CoO, CoOOH, Co(CH3COO)2, CoC2O4, and CoCO3. The use of the above-mentioned Co-containing compounds is more conducive to reducing surface impurities of lithium and improving cycle performance.

[0134] In some embodiments, in step S2, the Co-containing compound has a conventional particle size. Optionally, the Co-containing compound is present in the form of particles with a particle size of 0.01 to 10 μm, and optionally 0.1 to 1 μm. The addition of a Co-containing compound within this particle size range provides a better coating effect, is more conducive to reducing the amount of impurity lithium, and improves the cycling performance of the material.

[0135] In some embodiments, in step S2, the amount of Co in the coating layer is 100 to 16,000 ppm, preferably 1,000 to 13,000 ppm, based on the total weight of the positive electrode material. Using this amount of Co coating helps reduce the amount of stray lithium on the surface of the substrate particles and improves the cycle performance of the positive electrode material.

[0136] In some embodiments, in step S2, the sintering is carried out at a temperature of 500-800°C, preferably 550-750°C. In some embodiments, the sintering is carried out for 5-15 hours, preferably 5-10 hours. In some embodiments, the sintering is carried out in air or O2 atmosphere. The sintering process is beneficial to reduce the W in some W-containing compounds. 6+Further doping into the grain boundaries of the positive electrode material substrate particles; at the same time, it is also beneficial to allow the Co-containing compound to be coated on the surface of the positive electrode material substrate particles and interact with the miscellaneous lithium, thereby improving the material properties.

[0137] In some embodiments, in step S3, the B-containing compound is selected from one or more of BCl3, B2(SO4)3, B(NO3)3, BN, B2O3, BF3, BBr3, BI3, H2BO5P, H3BO3, C5H6B(OH)2, C3H9B3O6, (C2H5O)3B, and (C3H7O)3B. In some embodiments, in step S3, the coating amount of B is 100 to 2000 ppm, preferably 500 to 1500 ppm, based on the total weight of the positive electrode material. Coating with the B-containing compound can further reduce the content of impurity lithium on the surface of the material while increasing the capacity of the material. In addition, it can further improve the interfacial side reactions of the material and enhance the circulation, storage, and safety performance of the material.

[0138] In some embodiments, in step S3 , the substrate particles obtained from S1 or the product obtained from S2 are mixed with at least a B-containing compound and then sintered.

[0139] In some embodiments, in step S3, the Al-containing compound is selected from one or more of Al2O3, Al(OH)3, Al2(SO4)3, AlCl3, and Al(NO3)3. In some embodiments, in step S3, the Al coating amount is 100 to 3000 ppm, preferably 500 to 2000 ppm, based on the total weight of the positive electrode material. Coating with the Al-containing compound can further enhance the interfacial stability of the material particles and reduce interfacial side reactions, thereby further improving the material's recycling, storage, and safety performance.

[0140] In some embodiments, in step S3, the sintering is performed at a temperature of 200-500°C, optionally 200-400°C. In some embodiments, the sintering is performed for 5-15 hours, optionally 5-10 hours. In some embodiments, the sintering is performed in air or an O2 atmosphere. The sintering process of this invention facilitates coating the surface of the cathode material substrate particles with the B compound and / or Al compound, achieving a good coating effect.

[0141] In some embodiments, the precursor material is in the form of particles, and the volume particle size distribution has a diameter distance of 1.1 to 1.8, optionally 1.2 to 1.5. v 50 is 5 μm to 15 μm, optionally 5 μm to 10 μm. Using such precursor material particles is conducive to obtaining a desired positive electrode material with a larger compaction density, thereby facilitating the realization of a higher capacity.

[0142] In some embodiments, the mixing in step S2 or step S3 can be performed in a suitable device known to those skilled in the art, such as a plowshare mixer, a high-speed mixer, or an inclined mixer.

[0143] Another aspect of the present application provides a positive electrode material obtained by the above method.

[0144] Secondary batteries and electrical devices

[0145] Another aspect of the present application provides a secondary battery, comprising the positive electrode material of the present application, the positive electrode material obtained by the method of the present application, or the positive electrode sheet of the present application.

[0146] Secondary batteries include battery cells, battery modules, and battery packs.

[0147] Another aspect of the present application provides an electrical device including the secondary battery of the present application.

[0148] In addition, the battery cell, battery module, battery pack, and electric device of the present application will be described below with reference to the accompanying drawings as appropriate.

[0149] In one embodiment of the present application, a secondary battery is provided.

[0150] Typically, a secondary battery consists of a positive electrode, a negative electrode, an electrolyte, and a separator. During the battery's charge and discharge processes, active ions are inserted and removed between the positive and negative electrodes. The electrolyte conducts ions between the positive and negative electrodes. The separator, located between the positive and negative electrodes, primarily prevents short circuits between the positive and negative electrodes while allowing ions to pass through.

[0151] [Positive electrode]

[0152] Another aspect of the present application provides a positive electrode plate, comprising the positive electrode material of the present application or the positive electrode material obtained by the method of the present application.

[0153] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, and the positive electrode film layer includes the positive electrode material of the present application.

[0154] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive electrode current collector.

[0155] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0156] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, a vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorine-containing acrylate resin.

[0157] In some embodiments, the positive electrode film layer may further include a conductive agent. For example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0158] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0159] [Negative electrode]

[0160] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer optionally disposed on at least one surface of the negative electrode current collector. The negative electrode film layer includes a negative electrode active material.

[0161] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.

[0162] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base material. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer base material (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0163] In some embodiments, the negative electrode active material may be a negative electrode active material for a battery that is well known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxides, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxides, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0164] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0165] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0166] In some embodiments, the negative electrode film layer may optionally further include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0167] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0168] [Electrolytes]

[0169] The electrolyte conducts ions between the positive and negative electrodes. This application does not specify the type of electrolyte, and the electrolyte can be selected based on the needs. For example, the electrolyte can be liquid, gel, or solid.

[0170] In some embodiments, the electrolyte is an electrolyte solution comprising an electrolyte salt and a solvent.

[0171] In some embodiments, the electrolyte salt may be selected from lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, lithium tetrafluorooxalatophosphate.

[0172] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methylpropyl carbonate, ethylpropyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0173] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, and additives that improve battery high or low temperature performance.

[0174] [Isolation film]

[0175] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.

[0176] In some embodiments, the material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation. In some embodiments, the separator can also have one or more coatings.

[0177] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly through a winding process or a lamination process.

[0178] [Outer packaging]

[0179] In some embodiments, a secondary battery may include an outer packaging for encapsulating a positive electrode sheet, a negative electrode sheet, and an electrolyte. For example, the positive electrode sheet, the negative electrode sheet, and the separator may be stacked or wound to form a laminated or wound cell structure, which is encapsulated within the outer packaging. The electrolyte described in the first aspect of this application is used as the electrolyte, which is impregnated within the cell. The number of cells in a secondary battery may be one or more, and can be adjusted based on demand.

[0180] In one embodiment, the present application provides an electrode assembly. In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into the electrode assembly through a winding process or a lamination process. The outer packaging can be used to encapsulate the above-mentioned electrode assembly and electrolyte.

[0181] In some embodiments, the outer packaging of the secondary battery may be a soft bag, such as a bag-type soft bag. The material of the soft bag may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc. In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. This application has no particular restrictions on the shape of the secondary battery, which may be cylindrical, square, or any other arbitrary shape. For example, Figure 1 is a battery cell 5 of a square structure as an example.

[0182] In some embodiments, referring to Figure 2, the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0183] In some embodiments, battery cells may be assembled into a battery module. The battery module may contain one or more battery cells. The specific number may be selected by those skilled in the art based on the application and capacity of the battery module.

[0184] FIG3 shows an example battery module 4. Referring to FIG3 , within the battery module 4, multiple battery cells 5 may be arranged sequentially along the length of the battery module 4. Of course, they may also be arranged in any other manner. Furthermore, the multiple battery cells 5 may be secured together using fasteners.

[0185] Optionally, the battery module 4 may further include a housing having an accommodation space, and the plurality of battery cells 5 are accommodated in the accommodation space.

[0186] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art based on the application and capacity of the battery pack.

[0187] Figures 4 and 5 illustrate an example battery pack 1. Referring to Figures 4 and 5 , the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 can be placed over the lower case 3 to form an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.

[0188] In addition, the present application also provides an electrical device, which includes the secondary battery provided in the present application. The secondary battery can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but is not limited thereto.

[0189] As the electrical device, a battery cell, a battery module or a battery pack can be selected according to its usage requirements.

[0190] Figure 6 shows an example of an electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery, a battery pack or battery module can be used.

[0191] Another example device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is generally required to be lightweight and thin, and may use a secondary battery as a power source.

[0192] Example

[0193] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.

[0194] Example 1

[0195] 1. Preparation of cathode materials

[0196] -S0: Provide precursor material Ni 0.9 Co 0.05 Mn 0.05 (OH)2,D v 50 is 8.5μm, (D v90 -D v10 ) / D v50 is 1.35.

[0197] -S1: WO3 (particle size 50nm) and the precursor material are placed in a heated ball mill and ball milled (rotation speed 2000r / min, temperature 60°C) to obtain a mixture, wherein the W addition amount is 500ppm (based on the total weight of the precursor material). LiOH·H2O, Al2O3 and the above mixture are mixed so that the Li / Me molar ratio in the mixture is 1.15, and the Al addition amount is 500ppm (based on the total weight of the precursor material). The weight of the added M element (here is Al) / the weight of the added W element is 1:1. The above mixture is then sintered at 750°C in an O2 atmosphere for 20h to obtain substrate particles.

[0198] 2. Preparation of positive electrode sheet

[0199] The positive electrode material, polyvinylidene fluoride (PVDF), and conductive carbon (Super P) prepared above were added to methyl pyrrolidone (NMP) at a weight ratio of 90:5:5, and stirred in a drying room to prepare a positive electrode slurry (solid content of 97.44%). The positive electrode slurry was coated on aluminum foil at a temperature of 176 mg / cm 2 The positive electrode slurry is coated on the loaded material, and then dried and cold pressed to form the positive electrode sheet.

[0200] 3. Preparation of negative electrode sheet

[0201] The negative electrode active material artificial graphite, hard carbon, conductive agent acetylene black, binder styrene butadiene rubber (SBR), thickener carbon methyl cellulose sodium (CMC) were fully stirred and mixed in a deionized water solvent system according to a weight ratio of 90:5:2:2:1 to obtain a negative electrode slurry with a solid content of 96.5%. 2 The loading amount is coated on copper foil, dried, and cold pressed to obtain a negative electrode sheet.

[0202] 4. Isolation film

[0203] Commercially available polyethylene (PE) separator.

[0204] 5. Preparation of Electrolyte

[0205] Lithium hexafluorophosphate (LiPF6) was added to a mixed solvent of dimethyl carbonate (DMC), diethyl carbonate (DEC) and ethylene carbonate (EC) in a volume ratio of 1:1:1 and fully dissolved to obtain a usable electrolyte (lithium salt concentration of 1 mol / L).

[0206] 6. Preparation of batteries (full cells)

[0207] The obtained positive electrode sheet (20.8cm 2 )、Isolation film (22.4cm 2 )、Negative electrode (22.2cm 2 ) are stacked in order, with the separator between the positive and negative electrodes to provide isolation, and wound to obtain a bare cell. The bare cell is placed in an outer packaging, 0.5g of electrolyte is injected, and the cell is encapsulated to obtain a full battery.

[0208] 7. Preparation of button cells:

[0209] The positive electrode sheet (1.54 cm) prepared in the above 2 items is used. 2 ), lithium sheet as negative electrode, isolation membrane and the above electrolyte are assembled into button battery in button box.

[0210] 2. Performance Testing

[0211] 1. Characterization of the chemical composition of substrate particles:

[0212] A certain amount of powder was taken, digested with HF, and added to an ICP-OES instrument to detect the content of Li, Ni, Co, Mn, W, and M elements, and the specific element content molar ratio was obtained to obtain the specific chemical composition (as shown in Table 1).

[0213] 2. Detection method of W-enriched areas in grain boundaries:

[0214] The substrate particles were cut into sections using focused ion beam sputtering, and then observed in conventional mode under a scanning electron microscope and the particle cross-section was randomly selected. The selected position was then fixed and the scanning electron microscope voltage was adjusted to 15 kV. At this voltage, EDS element surface distribution was used to observe that the W element was concentrated at the grain boundaries of the substrate particles.

[0215] EDS elemental profiles were used to measure the change in W content within a primary particle from the grain boundary to the particle interior. For the substrate particles of Example 1, a decreasing W content was observed from the grain boundary to the interior of the primary particle. Within 40 nm of the grain boundary, the W content in the primary particle was 84% ​​(based on the total weight of W in the substrate particle).

[0216] 3. Verification of uniform doping of M elements in material particles:

[0217] Using focused ion beam sputtering or metallographic sample preparation, the substrate particles were sectioned and the internal morphology of the particles was observed using a conventional scanning electron microscope. Using EDS elemental distribution, it was observed that the M element was evenly distributed on the cross-section of the substrate particles.

[0218] 4. Material compaction density test method

[0219] 2g of cathode material is placed in a cylindrical mold with an inner radius of 8mm. Different pressures are applied to the material in the mold by a press until a double peak appears in the particle size distribution at a certain pressure. The compacted density is calculated using the following formula:

[0220] Compacted density = m / (π·R 2 ·ΔH)

[0221] Where m is the mass of the material being tested added to the mold, R is the inner radius of the mold, and ΔH is the height difference of the material before and after pressure is applied.

[0222] 5. Test method for initial gram capacity after power-off:

[0223] At a constant temperature of 25°C, charge to 4.3V at 0.1C, then charge at a constant voltage at 4.3V to a current ≤ 0.05mA, let stand for 2 minutes, the charge capacity at this time is recorded as C0, then discharge to 2.8V at 0.1C, the discharge capacity at this time is the initial gram capacity.

[0224] 6. Fully charged initial gram capacity test method:

[0225] Under a constant temperature environment of 25℃, let the new full battery stand for 5 minutes, discharge it to 2.8V at 1 / 3C, let it stand for 5 minutes, charge it to 4.25V at 1 / 3C, then charge it at constant voltage at 4.25V to a current of ≤0.05mA, let it stand for 5 minutes, and then discharge it to 2.8V at 1 / 3C. The discharge capacity at this time is the initial gram capacity.

[0226] 7. Fully electric 25 / 45℃ cycle performance test:

[0227] At a constant temperature of 25°C, charge the battery to 4.25V at 1C, then charge it at a constant voltage at 4.25V until the current is ≤0.05mA, let it stand for 5 minutes, and then discharge it to 2.8V at 1C. This is one cycle. The measured discharge capacity is recorded as D1. After 150 cycles, the measured discharge capacity is D 150 , calculate the capacity retention rate according to the following formula:

[0228] Capacity retention rate = (D 150 / D1)×100%,

[0229] And record it in Table 1.

[0230] Under a constant temperature of 45°C, the test was performed according to the above steps and the capacity retention rate was calculated and recorded in Table 1.

[0231] 8. Test of miscellaneous lithium content:

[0232] The impure lithium content of the material was tested using an acid-base titration method. 30g of sample was placed in 100ml of pure water, stirred for 30 minutes, then allowed to stand for 5 minutes. Filtered, 10ml of the supernatant was titrated with a 0.05mol / L hydrochloric acid standard solution. Using a pH electrode as the indicator electrode, the endpoint was determined by the sudden change in potential, and the impure lithium content of the positive electrode material was calculated.

[0233] 9. Full battery flatulence test:

[0234] The full battery cells with 100% state of charge (SOC) were stored at 70°C for 30 days. The volume of the cells before and after storage was measured using the water displacement method. The specific steps are as follows:

[0235] The tested cell is left to cool to room temperature, and the gravity on the cell is measured with a balance, which is F1. The cell is then completely immersed in deionized water (density is known to be 1g / cm 3 ), the balance shows F2, then the buoyancy F 浮 =F1-F2; then according to Archimedes principle F 浮 =ρgV 排 , calculate V 排 =(F1-F2) / ρg, which is the volume of the battery cell at this time.

[0236] The increase in the volume of the battery cell after storage relative to the volume of the battery cell before storage is calculated as the gas production; the ratio of the gas production to the battery cell capacity (the battery cell design capacity is 4Ah) is the gas production per unit capacity (mL / Ah), which is recorded in Table 2 below.

[0237] Example 2

[0238] Example 2 is substantially the same as Example 1, except that the particle size of the W source compound in step S1 is 100 nm, and the Li / Me molar ratio is modified to 1.1.

[0239] Example 3

[0240] Example 3 is substantially the same as Example 1, except that the particle size of the W source compound in step S1 is 56 nm, and the Li / Me molar ratio is modified to 1.05.

[0241] Example 4

[0242] Example 4 is substantially the same as Example 1, except that the particle size of the W source compound in step S1 is 68 nm, and the Li / Me molar ratio is modified to 1.2:1.

[0243] Example 5

[0244] Example 5 is basically the same as Example 1, except that the precursor composition in step S0 is Ni 0.64 Co 0.35 Mn 0.01 (OH)2. The particle size of the W source compound in step S1 is 77 nm.

[0245] Example 6

[0246] Example 6 is basically the same as Example 1, except that the precursor composition in step S0 is Ni 0.64 Co 0.01 Mn 0.35 (OH)2, the particle size of the W source compound in step S1 is 105 nm.

[0247] Example 7

[0248] Example 7 is basically the same as Example 1, except that the precursor composition in step S0 is Ni 0.8 Co 0.1 Mn 0.1 (OH)2, the particle size of the W source compound in step S1 is 89 nm.

[0249] Example 8

[0250] Example 8 is basically the same as Example 1, except that the precursor composition in step S0 is Ni 0.95 Co 0.025 Mn 0.025 (OH)2, the particle size of the W source compound in step S1 is 95 nm.

[0251] Example 9

[0252] Example 9 is basically the same as Example 1, except that in step S1, the amount of Al element added is 29000 ppm, the amount of W element added is 900 ppm, and the particle size of the W source compound is 120 nm.

[0253] Example 10

[0254] Example 10 is substantially the same as Example 1, except that in step S1, the amount of Al element added is 15000 ppm, the amount of W element added is 900 ppm, and the particle size of the W source compound is 85 nm.

[0255] Example 11

[0256] Example 11 is basically the same as Example 1, except that in step S1, the amount of Al element added is 5500 ppm, the amount of W element added is 19000 ppm, and the particle size of the W source compound is 90 nm.

[0257] Example 12

[0258] Example 12 is basically the same as Example 1, except that in step S1, the amount of Al element added is 5500 ppm, the amount of W element added is 89000 ppm, and the particle size of the W source compound is 110 nm.

[0259] Example 13

[0260] Example 13 is basically the same as Example 1, except that in step S1, the amount of Al element added is 5500 ppm, the amount of W element added is 155000 ppm, and the particle size of the W source compound is 90 nm.

[0261] Example 14

[0262] Example 14 is basically the same as Example 1, except that the Dv50 of the precursor in step S0 is 9.5, (D v90 -D v10 ) / D v50 is 1.5; the W source compound in step S1 is replaced with H2WO4 (particle size 94 nm), and the amount of W added is 1000 ppm, based on the total weight of the precursor material; the M source compound is ZrO2, and the added weight ratio of M to W is 1:0.33.

[0263] Example 15

[0264] Example 15 is basically the same as Example 1, except that the Dv50 of the precursor in step S0 is 9, (D v90 -D v10 ) / D v50 is 1.2; the W source compound in step S1 is replaced with Li2WO4 (particle size 68nm), and the amount of W added is 1500ppm, based on the total weight of the precursor material; the M source compound is TiO2, and the weight ratio of M to W added is 1:0.3.

[0265] Example 16

[0266] Example 16 is basically the same as Example 1, except that: the W source compound in step S1 is replaced with Li2WO4 (particle size 72nm), and the amount of W added is 1500ppm, based on the total weight of the precursor material; the M source compound is MgO, and the weight ratio of M to W added is 1:1.

[0267] Example 17

[0268] Example 17 is substantially the same as Example 1, except that the particle size of the W source compound in step S1 is 78 nm, the amount of Al added is 100 ppm, and the amount of W added is 100 ppm, based on the total weight of the precursor material.

[0269] Example 18

[0270] Example 18 is substantially the same as Example 1, except that the particle size of the W source compound in step S1 is 90 nm, the amount of Al added is 2000 ppm, and the amount of W added is 2000 ppm, based on the total weight of the precursor material.

[0271] Example 19

[0272] Example 19 is substantially the same as Example 1, except that the particle size of the W source compound in step S1 is 60 nm, the amount of Al added is 1000 ppm, and the amount of W added is 1000 ppm, based on the total weight of the precursor material.

[0273] Example 20

[0274] Example 20 is substantially the same as Example 1, except that the particle size of the W source compound in step S1 is 120 nm, the amount of Al added is 5000 ppm, and the amount of W added is 1000 ppm, based on the total weight of the precursor material.

[0275] Example 21

[0276] Example 21 is substantially the same as Example 1, except that the particle size of the W source compound in step S1 is 150 nm, the amount of Al added is 5000 ppm, and the amount of W added is 500 ppm, based on the total weight of the precursor material.

[0277] Example 22

[0278] Example 22 is substantially the same as Example 1, except that the particle size of the W source compound in step S1 is 80 nm, the amount of Al added is 5000 ppm, and the amount of W added is 2500 ppm, based on the total weight of the precursor material.

[0279] Comparative Example 1

[0280] Comparative Example 1 uses the positive electrode material in the prior art, whose chemical composition is LiNi 0.9 Co 0.05 Mn 0.05 O2, the remaining steps are the same as in Example 1.

[0281] Table 1 shows the relevant parameters of the substrate particles prepared in Examples 1-12:

[0282] Table 1

[0283]

[0284] *The weight percentage (wt.%) of W in the primary particles within a thickness of 40 nm from the grain boundary, based on the total weight of W doped in the substrate particles.

[0285] **Based on the total weight of the substrate particles.

[0286] ***Volume particle size distribution diameter = (D v 90-D v 10) / D v 50.

[0287] Table 2 shows the performance test results of the positive electrode materials in Examples 1-22:

[0288] Table 2

[0289]

[0290] As can be seen from Tables 1-2, by comparing the embodiments and comparative examples, the positive electrode material of the present invention has a higher compaction density, a higher capacity and better cycle performance (higher capacity retention rate in a wide temperature range), and has a lower amount of impure lithium, less gas production, and is safer.

[0291] Example 23

[0292] Example 23 is the same as Example 1 in step S1, except that after obtaining the substrate particles in step S1, the following step S2 is performed:

[0293] S2: The substrate particles obtained in S1 were mixed with H2WO4 (particle size 0.05 μm) to a W content of 2000 ppm (based on the total weight of the substrate particles). The mixture was sintered at 700°C in an O2 atmosphere for 15 h to obtain a positive electrode material having a W-containing coating layer.

[0294] Example 24

[0295] Example 24 is the same as Example 1 in step S1, except that after obtaining the substrate particles in step S1, the following step S2 is performed:

[0296] S2: The substrate particles obtained in S1 were mixed with CoO (particle size 0.1 μm) to a Co addition amount of 16,000 ppm (based on the total weight of the substrate particles). The mixture was sintered at 700°C in an O2 atmosphere for 15 h to obtain a positive electrode material having a Co-containing coating layer.

[0297] Example 25

[0298] Example 25 is the same as Example 1 in step S1, except that after obtaining the substrate particles in step S1, the following step S3 is performed:

[0299] S3: The substrate particles obtained in S1 are mixed with Al2O3 so that the amount of Al added is 3000 ppm (based on the total weight of the substrate particles), and the mixture is sintered at 500°C in an O2 atmosphere for 5 hours to obtain a positive electrode material having an Al coating layer.

[0300] Example 26

[0301] Example 26 is the same as Example 1 in step S1, except that after obtaining the substrate particles in step S1, the following step S3 is performed:

[0302] S3: The substrate particles obtained in S1 are mixed with B2O3 so that the added amount of B is 2000 ppm (based on the total weight of the substrate particles), and the mixture is sintered at 500°C for 5 hours in an O2 atmosphere to obtain a positive electrode material having a B-containing coating layer.

[0303] Example 27

[0304] Example 27 is the same as Example 1 in step S1, except that after the substrate particles are obtained in step S1, steps S2 and S3 as described below are performed:

[0305] S2: The substrate particles obtained in S1 were mixed with H2WO4 so that the amount of W added was 2000 ppm (based on the total weight of the substrate particles), and the mixture was sintered at 700°C in an O2 atmosphere for 15 h.

[0306] S3: The sintered product obtained in S2 was mixed with B2O3 so that the amount of B added was 2000 ppm, and the mixture was sintered at 500°C for 5 h in an O2 atmosphere to obtain a positive electrode material having a coating layer containing W and B.

[0307] Example 28

[0308] Example 28 is the same as Example 1 in step S1, except that after the substrate particles are obtained in step S1, steps S2 and S3 as described below are performed:

[0309] S2: The substrate particles obtained in S1 were mixed with CoO so that the amount of Co added was 16000 ppm (based on the total weight of the substrate particles). The mixture was sintered at 700° C. for 15 h in an O 2 atmosphere.

[0310] S3: The sintered product obtained in S2 was mixed with B2O3 so that the amount of B added was 2000 ppm (based on the total weight of the substrate particles), and the mixture was sintered at 500°C in an O2 atmosphere for 5 hours to obtain a positive electrode material having a coating layer containing Co and B.

[0311] Example 29

[0312] Example 29 is the same as Example 1 in step S1, except that after the substrate particles are obtained in step S1, steps S2 and S3 as described below are performed:

[0313] S2: The substrate particles obtained in S1 were mixed with CoO and H2WO4 to a Co content of 16,000 ppm and a W content of 2,000 ppm, both based on the total weight of the substrate particles. The mixture was sintered at 700°C in an O2 atmosphere for 15 h.

[0314] S3: The sintered material obtained in S2 is mixed with Al2O3 and B2O3, so that the added amount of Al is 3000ppm, the added amount of B is 2000ppm, the Al coating amount: the B coating amount is 1.5:1, and the mixture is sintered at 500°C in an O2 atmosphere for 5h to obtain a positive electrode material with a coating layer.

[0315] Examples 30-44

[0316] The difference between Example 29 and Example 29 is that the contents of the elements in steps S2 and S3 are adjusted. The content details and performance test data are shown in Table 3-4 below.

[0317] The presence and thickness of the coating layer can be observed using a scanning electron microscope. The coating layer is visible as a separate layer outside the substrate particles. The content of various elements in the coating layer is quantified using EDS elemental distribution analysis using a scanning electron microscope.

[0318] Table 3

[0319]

[0320]

[0321] Table 4

[0322]

[0323]

[0324] As can be seen from Tables 3-4, after coating, the capacity and cycle performance of the positive electrode material of the present invention are further improved, the amount of surface impurities of lithium is reduced, and flatulence is significantly improved, thereby improving the safety performance of the battery.

[0325] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A positive electrode material comprising substrate particles with a chemical composition of formula (I): Li 1+a [Ni x Co y Mr z M b W c ]O2 (I) in, M is selected from one or more of Mo, Zr, Al, Ti, Sb, Nb, Te, Mg, Al, Ca, Zn, and Sr, 0.6 ≤ x < 1, 0 < y < 0.4, 0 < z < 0.4, 0 < a < 0.2, 0 < b < 0.1, 0 < c < 0.1, x + y + z + b + c = 1; and W is enriched at the grain boundaries of the substrate particles.

2. The positive electrode material according to claim 1, wherein the formula (I) satisfies one or more of the following conditions (1) to (8): (1) M is selected from one or more of Zr, Al, Mg, and Ti; (2)0.8≤x<1; (3)0<a<0.08; (4)0<b<0.018; (5)0<c<0.0013; (6) b:c = 0.076 to 384, optionally b:c = 5 to 69, more optionally b:c = 13 to 69; (7) (1 + a):(x + y + z) = 1.01 to 1.25, optionally (1 + a):(x + y + z) = 1.05 to 1.15; (8) The doping weight of the M element ≥ the doping weight of the W element, optionally the weight ratio of the M element to the W element is 1:(0.1 to 1), more optionally 1:(0.1 to 0.5).

3. The positive electrode material according to claim 1 or 2, wherein in the substrate particles, the W content within a thickness of 40 nm from the grain boundaries is at least 80% by weight, optionally at least 90% by weight, based on the total weight of W in the substrate particles.

4. The positive electrode material according to any one of claims 1 to 3, wherein based on the total weight of the substrate particles, the W content in the substrate particles is 100 to 200000 ppm, optionally 100 to 3000 ppm, more optionally 500 to 2500 ppm.

5. The positive electrode material according to any one of claims 1 to 4, wherein the volume particle size distribution diameter (D v 90-D v 10) / D v 50 is 1.1 to 1.8, optionally 1.2 to 1.5, more optionally 1.25 to 1.

45.

6. The positive electrode material according to any one of claims 1 to 5, further comprising a coating layer provided on the surface of the substrate particles, the coating layer containing at least one of the elements W, Co, Al, and B; optionally, the coating layer contains at least the element W and / or B; more optionally, the coating layer includes the elements W, Co, Al, and B.

7. The positive electrode material according to claim 6, wherein the coating layer satisfies one or more of the following conditions (1) to (5): (1) The coating layer contains 100 ppm to 2000 ppm, optionally 500 ppm to 1000 ppm of the W element, based on the total weight of the substrate particles; (2) The coating layer contains 100 ppm to 16000 ppm, optionally 1000 ppm to 13000 ppm of the Co element, based on the total weight of the substrate particles; (3) The coating layer contains 100 ppm to 3000 ppm, optionally 500 ppm to 2000 ppm of the Al element, based on the total weight of the substrate particles; (4) The coating layer contains 100 ppm to 2000 ppm, optionally 500 ppm to 1500 ppm of the B element, based on the total weight of the substrate particles; (5) The coating layer contains W, Co, Al and B elements and the total amount of these four elements is 1000 to 22000 ppm, preferably 1000 to 15000 ppm, based on the total weight of the substrate particles.

8. A method for preparing a positive electrode material, the positive electrode material comprising substrate particles having a chemical composition of formula (I): Li 1+a [Ni x Co y Mr z M b W c ]O2 (I) in, M is selected from one or more of Mo, Zr, Al, Ti, Sb, Nb, Te, Mg, Al, Ca, Zn and Sr, 0.6≤x<1,0 <y<0.4,0<z<0.4,0<a<0.2,0<b<0.1,0<c<0.1,x+y+z+b+c=1; and W is enriched at the grain boundaries of the substrate particles; The method comprises the following steps: -S0: Provide a precursor material with a chemical composition of Ni x Co y Mn z (OH)2, 0.6 ≤ x < 1, 0 < y < 0.4, 0 < z < 0.4, and x + y + z = 1, - S1: Grind and mix the precursor material and the W source compound, then add the Li source compound and the M source compound thereto and mix thoroughly, and sinter the mixture to obtain the substrate particles.

9. The method according to claim 8, wherein the particle size of the W source compound particles is 20 to 500 nm, optionally 50 to 300 nm; and / or wherein the W source compound is selected from one or more of WO3, H2WO4, Li2WO4, (NH4)2WO4, MgWO4 and Zr(WO3)2; optionally, one or more of WO3, H2WO4 and Li2WO4; and / or The added amount of W element is 100-200000 ppm, optionally 100-3000 ppm, optionally 500-2500 ppm, based on the total weight of the precursor material.

10. The method according to claim 8 or 9, wherein the M source compound is selected from sulfates, nitrates, chlorides, carbonates, oxides, hydroxides, oxalates and acetates containing the M element, and is optionally an oxide of the M element; Optionally, the M element is one or more of Zr, Al, Mg and Ti; Optionally, the added amount of the M element is 100 to 5000 ppm, optionally 500 to 3000 ppm, based on the total weight of the precursor material.

11. The method according to any one of claims 8 to 10, wherein step S1 satisfies at least one of the following conditions: (1) The added weight ratio of the M element to the W element is 1:(0.1-1), optionally 1:(0.1-0.5); (2) The ratio of the molar amount of Li atoms to the total molar amount of Ni, Co, and Mn atoms is set to 1.01 to 1.25, and optionally 1.05 to 1.

15.

12. The method according to any one of claims 8 to 11, wherein the grinding and mixing is carried out by mechanical milling or ball milling; optionally, the grinding and mixing is carried out in a ball mill, optionally in a heated ball mill; Optionally, the grinding speed is 500-3000 r / min, optionally 1000-2000 r / min; or 800-1500 r / min; Optionally, the grinding and mixing is carried out at a temperature of 30-100°C, optionally 40-60°C.

13. The method according to any one of claims 8 to 12, further comprising the step of providing a coating layer on the surface of the substrate particles, comprising: - S2: mixing the substrate particles obtained in S1 with a W-containing compound and / or a Co-containing compound and sintering; and / or - S3: The substrate particles obtained from S1 or the sintered product obtained from S2 are mixed with an Al-containing compound and / or a B-containing compound and then sintered.

14. The method according to claim 13, wherein step S2 satisfies one or more of the following conditions: (1) The W-containing compound is selected from one or more of WO3, H2WO4, Li2WO4, (NH4)2WO4, MgWO4, and Zr(WO3)2; (2) The amount of W element added is 100 to 2000 ppm, optionally 500 to 1000 ppm, based on the total weight of the precursor material.

15. The method according to claim 13 or 14, wherein step S2 satisfies one or more of the following conditions: (1) The Co-containing compound is selected from one or more of Co3O4, Co(OH)2, CoO, CoOOH, Co(CH3COO)2, CoC2O4, and CoCO3; (2) The amount of Co added is 100 to 16,000 ppm, preferably 1,000 to 13,000 ppm, based on the total weight of the precursor material.

16. The method according to any one of claims 13 to 15, wherein in step S3, the Al-containing compound is selected from one or more of Al2O3, Al(OH)3, Al2(SO4)3, AlCl3 and Al(NO3)3; and / or The amount of Al added is 100 to 3000 ppm, preferably 500 to 2000 ppm, based on the total weight of the precursor material.

17. The method according to any one of claims 13 to 16, wherein in step S3, the B-containing compound is selected from one or more of BCl3, B2(SO4)3, B(NO3)3, BN, B2O3, BF3, BBr3, BI3, H2BO5P, H3BO3, C5H6B(OH)2, C3H9B3O6, (C2H5O)3B and (C3H7O)3B, and / or The addition amount of B is 100 to 2000 ppm, preferably 500 to 1500 ppm, based on the total weight of the precursor material.

18. The method according to any one of claims 8 to 17, wherein the volume particle size distribution of the precursor material has a diameter distance of 1.1 to 1.8, optionally 1.2 to 1.5; and / or The D of the precursor material v 50 is 5 μm to 15 μm, optionally 5 μm to 10 μm. 19 . A secondary battery comprising the cathode material according to claim 1 or the cathode material obtained by the method according to claim 8 .

20. An electric device comprising the secondary battery selected from the group consisting of:

Citation Information

Patent Citations

  • Lithium secondary battery

    CN103563139A

  • Metal composite hydroxide, method for producing same, positive electrode active material for nonaqueous electrolyte secondary batteries, method for producing said positive electrode active material, and nonaqueous electrolyte secondary battery using said positive electrode active material

    CN111094188A

  • Positive electrode material and preparation method and application thereof

    CN111384377A

  • Preparation method of nickel cobalt lithium manganate ternary positive electrode material

    CN114204011A

  • High-nickel ternary positive electrode material as well as preparation method and application thereof

    CN114436347A